Implementation of Teaching at The Right Level (TaRL) Approach on Enhancing Students’ Writing Ability in 8th Grade of Junior High School - Annisa Rahmasari; Gusti Nur Hafifah; Nur Afifah (PROCEEDING UMSURABAYA, 2026)
This classroom action research examines the implementation of the Teaching at the Right Level (TaRL) approach to improve the writing of 8G grade students at a public junior high school in Surabaya during the 2024–2025 academic year. The pre-cycle evaluation at the beginning of the learning process showed that only 36.36% of students had mastery, with an average score of 60.22, suggesting that there was still much space for improvement. As a result, lesson plans and student worksheets catered to different ability levels were created using the TaRL approach. The average student score rose significantly to 85.30 after the adoption, indicating a notable improvement in writing ability. The findings show that the TaRL model promotes equitable learning and increases student engagement, particularly when paired with differentiated learner worksheet (LKPD) and group activities. Overall, the study finds that by addressing a variety of learning needs and encouraging collaborative learning environments, the TaRL strategy not only raises student response but also improves academic achievement.